Quantum-chemical study of electronically excited states ofprotolytic forms of vanillic acid; Proceedings of SPIE; Vol. 9810 : Atomic and Molecular Pulsed Lasers XII - Vusovich O. V.; Tchaikovskaya O. N.; Sokolova I. V.; Vasileva N. Y. (Photonics of Optical Materials, Optoelectronics, 2015)
Title screen